2019
DOI: 10.1186/s12939-019-1001-7
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket expenditure and distress financing on institutional delivery in India

Abstract: Background: Despite large investment in central and state sponsored schemes for maternal care, out-of-pocket expenditure (OOPE) and catastrophic health spending (CHS) on institutional delivery remain high over time, across states and across socioeconomic groups. Though many studies have examined the OOPE and CHS, few studies have examined the nature and extent of distress financing on institutional delivery in India. Data: Data from the fourth round of National Family Health Survey (NFHS 4), 2015-16 was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…Studies show that the average delivery cost in the caesarean section is many times higher than the normal delivery. 25,26 Consistence to previous studies, this study also shows that the average caesarean delivery cost is almost double than non-caesarean delivery. In private hospitals, this difference is more than three times higher.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Studies show that the average delivery cost in the caesarean section is many times higher than the normal delivery. 25,26 Consistence to previous studies, this study also shows that the average caesarean delivery cost is almost double than non-caesarean delivery. In private hospitals, this difference is more than three times higher.…”
Section: Discussionsupporting
confidence: 72%
“…Study reveals that sometimes they had to borrow money or sell their assets to meet the delivery cost. 26 Moreover, the benefits of using caesarean sections are yet to be a debatable issue on maternal and child health perspectives. The findings in this study show that mean z-score concentrations on all the three anthropometric indicators of children (i.e., stunting, underweight, and wasting) were close to normal for the non-caesarean children than those of caesarean children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although health system depends on state policy, reproductive services including antenatal care and delivery are provided mostly for free or at nominal cost in public health centers in India [ 15 ]. On the other hand, patients have to pay a significant amount of out-of-pocket (OOP) cost in private facilities because the governments neither regulate the service-fee charged by private providers nor do they support the cost for service utilization in the private facilities except for some empanelled ones in special government schemes such as Ayushman Bharat or Janani Suraksha Yojana (JSY) that aim to ensure accessibility to the health service of the poor and the vulnerable [ 16 ]. Therefore, there is a big gap in OOP expenditure for C-section between public and private facilities [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of CHE25 in 2017 was nine times greater in private sector than in public sector. Studies in India and several LMICs have reported that OOPE was greater for private sector utilization, including for in-patient care [13,20,32,49,[58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%